Experimental verification of Hyper-V performance isolation level - Rzecki, Krzysztof; Niedźwiecki, Michał; Sośnicki, Tomasz; Martyna, Andrzej (Computer Science, 2014)
<!– P margin-bottom: 0.21cm; direction: ltr; color: rgb(0, 0, 0); line-height: 115%; P.western font-family: "Apolonia"; font-size: 12pt; P.cjk font-size: 12pt; P.ctl font-family: "FreeSans"; font-size: 12pt; A:link –> The need for cost optimization in a broad sense constitutes the basis of operation of every enterprise. In the case of IT structure, which is present in almost every field of activity these days, one of the most commonly applied technologies leading to good cost-to-profit adjustment is virtualization. It consists in locating several operational systems with IT systems on a single server. In order for such optimization to be carried out correctly it has to be strictly controlled by means of allocating access to resources, which is known as performance isolation. Modern virtualizers allow to set up this allocation in quantitative terms (the number of processors, size of RAM, or disc space). It appears, however, that in qualitative terms (processor’s time, RAM or hard disc bandwidth) the actual allocation of resources does not always correspond with this configuration. This paper provides an experimental presentation of the achievable level of performance isolation of the Hyper-V virtualizer.